Perlindungan Hukum Pengetahuan Tradisional Sanro - Fitriani Jamaluddin; Muhammad Ashabul Kahfi; Nurul Adliyah; Wawan Haryanto (Jurnal Ilmiah Kebijakan Hukum, 2023)
This study aims to find out about the legal protection of Sanro Traditional Knowledge in South Sulawesi, and to analyze the concept of benefit sharing as a protection for Sanro traditional knowledge. This research is normative research, with a statue approach, while the data source used is secondary data in the form of statutory regulations related to Traditional Knowledge. The results of this study indicate that statutory regulations relating to Traditional Knowledge are not sufficient in providing protection. So, one of the concepts that can be applied in the protection of Traditional Knowledge is by using the concept of benefit sharing. The concept of benefit sharing that used not only emphasize the economic aspect, but also the moral aspect, which is the recognition of the existence of the Traditional Knowledge.